It's what's on the inside that counts: stress physiology and the bacterial microbiome of a wild urban mammal. Issue 1913 (23rd October 2019) - Stothart, Mason R.; Palme, Rupert; Newman, Amy E. M.
Abstract : The microbiome's capacity to shape the host phenotype and its mutability underlie theorization that the microbiome might facilitate host acclimation to rapid environmental change. However, when environmental change occurs, it is unclear whether resultant microbiome restructuring is proximately driven by this changing external environment or by the host's physiological response to this change. We leveraged urbanization to compare the ability of host environment (urban or forest) versus multi-scale biological measures of host hypothalamic–pituitary–adrenal (HPA) axis physiology (neutrophil : lymphocyte ratio, faecal glucocorticoid metabolites, hair cortisol) to explain variation in the eastern grey squirrel ( Sciurus carolinensis ) faecal microbiome. Urban and forest squirrels differed across all three of the interpretations of HPA axis activity we measured. Direct consideration of these physiological measures better explained greater phylogenetic turnover between squirrels than environment. This pattern was strongly driven by trade-offs between bacteria which specialize on metabolizing digesta versus host-derived nutrient sources. Drawing on ecological theory to explain patterns in intestinal bacterial communities, we conclude that although environmental change can affect the microbiome, it might primarily do so indirectly by altering host physiology. We demonstrate that the inclusion and careful consideration of dynamic, rather than fixed (e.g. sex), dimensions of host physiology are essential for the study of host–microbe symbioses at the micro-evolutionary scale.